Synthesis and dielectric properties of PAN-based Na+ ion polymer electrolytes. (2022) - Jyothi, N. Krishna; Rao, K. Tarakeswara; Kumar, V. Naveen; Kiran, M. Gnana; Deepthi, K.; Rao, M.C.; Kumar, K. Vijaya; Inthiyaz, Syed
Abstract: Polymer electrolytes have become more prominent due to various important applications in electro-chemical appliances and other rechargeable cells. Polymer polyacrylonitrile (PAN) based sodium iodide (NaI) doped composite conducting polymer electrolyte was synthesized by solution cast method. The prepared conducting polymer electrolyte films were mechanically stable and transparent. Complexation of the composition, interaction between cation of salt and nitrogen of PAN and vibrational modes of ions was confirmed by Fourier transform infrared spectroscopic (FTIR) studies. The electrical conductivity and dielectric properties information was obtained by LCR meter through impedance study for the prepared electrolyte films. Dielectric constant, dielectric loss and AC conductivity were observed for PAN: NaI (90:10; 80:20; 70:30; 60:40) composition. The dielectric behavior was analyzed using ε 1 and ε 11 values. The ε 1 and ε 11 values are high at lesser frequencies and less at higher frequencies.